2021
DOI: 10.1155/2021/6665704
|View full text |Cite
|
Sign up to set email alerts
|

N1, N12-Diacetylspermine Is Elevated in Colorectal Cancer and Promotes Proliferation through the miR-559/CBS Axis in Cancer Cell Lines

Abstract: N1, N12-Diacetylspermine (DiAcSpm) has been reported to be upregulated in the urine of cancer patients. Mass spectrometry has shown elevated DiAcSpm expressions in colorectal cancer (CRC) tissues. However, the diagnostic application of DiAcSpm is not available due to a lack of diagnostic grade antibodies. Also, its biological roles in CRC cells remain unexplored. In the present study, we developed an antibody that directly detected DiAcSpm expression in paraffin-embedded tissues. We also characterized its biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Several independent studies have confirmed CBS protein expression in the above colon cancer lines, and extended the findings to additional colon cancer cell lines (e.g. DLD-1 and SW480) as well [ 27 , 38 , 49 , 51 , 52 , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] ].…”
Section: Cbs Expression In Various Cancer Cell Linesmentioning
confidence: 65%
See 1 more Smart Citation
“…Several independent studies have confirmed CBS protein expression in the above colon cancer lines, and extended the findings to additional colon cancer cell lines (e.g. DLD-1 and SW480) as well [ 27 , 38 , 49 , 51 , 52 , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] ].…”
Section: Cbs Expression In Various Cancer Cell Linesmentioning
confidence: 65%
“…However, clearly, high CBS expression has not been observed in all rapidly proliferating cell types studied, so proliferation, by itself , can not be the sole driving factor. Nevertheless, in some cases, a close correlation has been found between CBS upregulation and increased cell proliferation; for instance, in human colon cancer cell lines treated with increasing concentrations of the polyamine N12-diacetylspermine [ 98 ]. The potential role of hypoxia as a CBS-inducing or enhancing factor, has been explored by multiple investigators, and yielded variable results.…”
Section: Cbs Expression In Various Cancer Cell Linesmentioning
confidence: 99%
“…One of the well explored spermine derivative in cancer is N 1 , N 12 -Diacetylspermine (DiAcSpm), which is produced by two rounds of acetylation of spermine, catalyzed by SAT1/2. Studies have demonstrated the prognostic value of DiAcSpm in lung cancer, colorectal cancer and breast cancer [14][15][16]. In this review, we are going to review the changes in spermine level in different human cancers and the possible applications of spermine in cancer treatment regimes in a clinical setup.…”
Section: Introductionmentioning
confidence: 99%
“…89 N1, N12-Diacetylspermine can up-regulate the expression of CBS and promote the proliferation of colorectal cancer cell lines SW480 and Caco2, while miR-559 can target and inhibit CBS and inhibit the proliferation of the cells. 138 These opposite results of CBS may be caused by the difference in cell lines, and AOAA, as a pyridoxal phosphate-dependent enzymes inhibitor, showed an inhibitory effect on both CBS and CSE. 139,140 3-MST is highly expressed in murine colon cancer cell line CT26.…”
Section: Endogenous H 2 S and Hepatomamentioning
confidence: 99%
“…MiR-24-3p, miR-203, and miR-376a can target CBS to induce apoptosis, and miR-559 can also target CBS to inhibit cell proliferation. 130,138,173,174 MiR-30 family can induce oxidative stress by inhibiting CSE, 175,176 while miR-216a also directly targeted CSE to inhibit its expression. 177 And miR-4137 can inhibit both CBS and CSE in BC to yield a tumour-suppressing effect.…”
Section: Microrna and Transcription Factorsmentioning
confidence: 99%